La politica cambia, i valori restano? Una ricerca quantitativa e qualitativa sulla cultura politica in Toscana - De Sio, Lorenzo (Strumenti per la didattica e la ricerca, 2011)
How do Tuscans see politics? What is their relationship with it? Is there something different from the «red subculture» of the First Republic? Articulated answers to these questions emerge from this research commissioned by the Tuscan Regional Authority and conducted by the Centro Italiano Studi Elettorali with a mixed quantitative and qualitative approach. On the one hand, associative participation - expression of a deeply embedded tradition - is alive and kicking. On the other hand, we can see a decline in political participation, alongside elements of tension in the relation between citizens, parties and institutions. These are the inevitable signs of the great symbolic and organisational changes that have affected the mass parties; they must now address new challenges if they want to maintain the vital dialogue that the Tuscans demand from their political class.